Pembuatan Jingle Tempe Sanan Enak Tenan Sebagai Media Promosi Untuk Meningkatkan Daya Saing UMKM Tempe Sanan - Suprihatin, Endang Wara; Sumarwahyudi; Pristiati, Tutut; Zandra, Rully Aprilia; Prasetyo, Yunanto Adi; Handayani, Silvy; Isfa'lan, Widad (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2025)
Tempe Sanan, one of the well-known local products from Malang, is currently facing challenges in branding and market competitiveness despite its high quality. This is especially true in the midst of the growing trend of online-based promotions, which appear to be more effective and efficient. This community service program aims to enhance the competitiveness and brand awareness of Tempe Sanan through a song, packaged in the form of a jingle. The creation of a jingle as a promotional medium was chosen because it serves as a concise, simple, and effective alternative for promotion that can be played anytime and anywhere The jingle is designed to be catchy and appealing, combining local cultural elements with Javanese lyrics and a blend of diatonic and pentatonic musical instruments. Its creation employed a participatory approach, involving local MSME (Micro, Small, and Medium Enterprise) actors in developing a culturally rich jingle. The outcomes of the activity include: 1) The creation of a jingle titled "Tempe Sanan Enak Tenan" (Tempe Sanan is Really Delicious);2) Dissemination via WhatsApp and recording in MP3 format, played at Primkobti Bangkit Usaha Kampung Sanan;3) Socialization and public presentation of the jingle at the Porprov East Java exhibition. The conclusion of this community service initiative emphasizes the effectiveness of music as a branding tool for local MSMEs, which is essential for enhancing their market competitiveness.